Biocatalytic and Biological Activities of Cassia Occidentalis Mediated Silver Nanoparticles - Singh, Shashika; Mohanlall, Viresh (Trends in Sciences, 2022)
Silver nanoparticles (AgNPs) were synthesized using the leaf extracts from Cassia occidentalis. The reactions were marked by a distinct colour change and the formation of AgNPs was monitored by measuring the UV-Vis spectra. The morphology and crystalline phase of the metal nanoparticles were determined using Transmission Electron Microscopy (TEM) and Scanning Electron Microscopy (SEM) with Energy Dispersive X-ray analysis (EDX) and Fourier-Transform-Infrared Spectroscopy (FTIR). The biocatalytic activity of the AgNPs against nitrifying compounds was determined using 4-nitrophenol and 4-nitroalanine. The biological screening involved analyzing the AgNPs effectiveness against gram-negative and gram-positive bacteria (Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa, Bacillus cereus and Enterococcus faecalis). The AgNPs displayed minimal inhibition at low concentrations ranging from 25 to 50 μg/mL. The toxicity of the AgNPs was tested using the brine shrimp assay and was observed as non-toxic with a nearly zero mortality rate. The AgNPs exhibited an antioxidant potential of 70.90 % inhibition at 1000 µg/mL. C. occidentalis is noted as a potential bioresource for synthesizing AgNPs with applications as antibacterial, antioxidant and biocatalytic agents. HIGHLIGHTS The addition of Ag nanoparticles to C. occidentalis plant extracts resulted in the formation of AgNPs-C. occidentalis complexes The AgNPs-C. occidentalis complexes were characterized using Transmission Electron Microscopy, Scanning Electron Microscopy with EDX, UV-Vis spectrophotometry and IR spectroscopy These AgNPs-C. occidentalis complexes were very stable and showed antibacterial activity against a range of tested gram-positive and gram-negative bacteria at low doses, thus proving to be good antimicrobial agents The AgNPs-C. occidentalis complexes showed higher scavenging activity than leaf extracts of C. occidentalis. The AgNPs have increased catalytic ability for the reduction of 4-nitrophenol and 4-nitroalanine after a 30 min time interval GRAPHICAL ABSTRACT